The effect of contact frequency with customers on relationship satisfaction - Lia Jung; Seolwoo Park (Global Business & Finance Review (GBFR), 2020)
Purpose: This study is to examine the moderating role of contact mode and customer attachment style on the effects of contact frequency on relationship satisfaction. Design/methodology/approach: To explain this phenomenon, literature reviews about contact frequency, contact mode, relationship satisfaction, the moderating effect of contact mode (personal vs.impersonal), and attachment style (anxious vs.avoidant).SEM (Structure Equation Model) was suggest to check these relationships using PLS. Findings: Bootstrapping analysis was performed using process macros to find the relationship between contact frequency and relationship satisfaction.As a results, Contact frequency does not significantly affect satisfaction with a company; however, this independent variable affects satisfaction with a company via satisfaction with the service provider.Anxious people are known to be dependent, while avoidant people are independent, so customers' attachment styles influence their relationship satisfaction.Personal contact modes, such as by telephone, are found to be more positive than impersonal contact modes, such as group email, for relationship satisfaction.The results of this study show that customers prefer personal contact to impersonal contact.Moreover, for both anxious and avoidant customers, frequent contact has positive effects on customer satisfaction with service providers and organizations. Research limitations/implications: This study provide two contributions.First, it confirmed the mediation effect of the customer-service-provider relationship.Customers' satisfaction with a company depends on their satisfaction with its service providers.Second, this study identified a moderating role played by the contact mode and the customer's attachment style.In regard to future research, it would be nice to add cases for increasing customer-satisfaction level with service firms and to focus on other industries to expand current research findings. Originality/value: The findings provide customer segmentation criteria and guidelines for effective relationship marketing activities in service field.
Keywords: 650; Contact Frequency; Contact Mode; Attachment Style; Relationship Satisfaction